2023
DOI: 10.1108/ajim-01-2023-0016
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-sharing attitude and behavior of civil servants: motivations behind rewards

Kristy Lam,
Elaine W.S. Kong,
Dickson K.W. Chiu
et al.

Abstract: PurposeTo a large extent, knowledge in government workplaces resides within the hierarchy as it provides unique services to the public. Governments should preserve and pass on valuable and irreplaceable knowledge in providing their services through learning by sharing. Yet, sharing requires time and effort. This study examines the motivations of civil servants to share knowledge and their knowledge-sharing behaviors.Design/methodology/approachThe authors conducted an online survey to collect quantitative data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Results indicate that the research growth rate is expected to gradually increase and reveal countries and topics of research focus. Readers may be interested in reading recent articles on curriculum development for the Master of Public Administration (Ho et al, 2023a), urban governance (Zhang et al, 2023), IoT as a societal transformer (Chohan et al, 2023), open government data (Dai et al, 2023;Wu et al, 2022;Wang et al, 2023c) and knowledge management in governments (Lam et al, 2023). Khan et al (2024a) performed a systematic review and found a significant impact of information creditability on the information adoption behavior of social media users.…”
Section: Public and Culturementioning
confidence: 99%
“…Results indicate that the research growth rate is expected to gradually increase and reveal countries and topics of research focus. Readers may be interested in reading recent articles on curriculum development for the Master of Public Administration (Ho et al, 2023a), urban governance (Zhang et al, 2023), IoT as a societal transformer (Chohan et al, 2023), open government data (Dai et al, 2023;Wu et al, 2022;Wang et al, 2023c) and knowledge management in governments (Lam et al, 2023). Khan et al (2024a) performed a systematic review and found a significant impact of information creditability on the information adoption behavior of social media users.…”
Section: Public and Culturementioning
confidence: 99%